Generic skills in the curriculum of the Bachelor of Library Science at the Autonomous University of San Luis Potosi, Mexico - Martínez Rider, Rosa María (2012)
We present the results of a study on the development of generic skills in the student population of the legislation of the race's degree in Library Science from the Autonomous University of San Luis Potosí (UASLP).